Evaluation Cultural Content on English Textbook Used by EFL Students in Indonesia - Mutiara Ayu (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
Choosing an acceptable textbook is not a simple task since it may be a key component in most language program. It serves as language input and language practice for learners. It also provides the premise for content lesson, the variety of language practice for learner, and serves as a supplement for teacher’s instruction. Teaching and learning a language without knowing its culture are useless. Culture should be taught to the students so as to dig deeper their language potential in learning English. Therefore, a textbook which is often utilized by teachers as a medium to show and help them within the process of teaching and learning should have a significant part in disseminating cultures. Culture is split into three categories: source culture, target culture, and international target culture. Some problems arise whether to keep up the source culture because the dominant part or to clarify more about the target culture. Also, the ignorance of cultural teaching commonly happens in language classroom. Thus, this paper will evaluate and explore how important cultural literacy in EFL teaching is and discuss which culture should be taught in EFL.